Peran Dan Pemikiran Syekh Nawawi Al-Bantani Dalam Pengembangan Keilmuan Islam Nusantara - Anggraini, Fitri (PKBM DAARUL AHKAAM, 2025)
Sheikh Nawawi al-Bantani was one of the 19 th-century Indonesian scholars who had a major influence on the development of Islamic scholarship, both locally and internationally. This article aims to examine the role and contribution of Sheikh Nawawi al-Bantani in the development of Islamic thought, particularly in the fields of education, fiqh, and tafsir. The research method used is library research with a historical and conceptual approach, through analysis of Sheikh Nawawi's works and other supporting literature. The results of the study show that Sheikh Nawawi al-Bantani played an important role in strengthening the tradition of moderate Islamic scholarship rooted in classical heritage, while remaining relevant to the social context of Muslims in the archipelago. His thoughts not only contributed to the strengthening of Islamic boarding school institutions, but also shaped a tolerant and moral character of religious diversity.